ANALISIS PENGARUH COUNTRY OF ORIGIN PERCEPTION, PERCEIVED QUALITY DAN CONSUMER PERCEPTION TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI PADA OLI FASTRON DI KOTA SEMARANG) - Angela Faraditta; Mudiantono - (Conference In Business, Accounting, And Management (CBAM), 2015)
Intense competition has made oil Fastron who is originally Indonesia’s Lubricants has percentage decreasing of Top Brand Index (TBI) for last three years and always be in the last rank for the Top Five Lubricants in Indonesia defeated by products from abroad. Top Brand Index (TBI) which has three main indicators, which is top of mind awareness, last used, and future intention. The purpose of this study is to determine the influence of variables Country Of Origin Perception, Perceived Quality, Consumer Perception as Independent Variabel and Brand Image as Intervening Variable on Purchase Intention as Dependent Variable expected later can increase the percentage of TBI with a focus indicator future intention. The results showed that an independent third variable has a positive influence on Brand Image; and Brand Image has a positive influence on Purchase Intention. However, for the direct effect of the three independent variables on the dependent variable only Perceived Quality which has a positive influence on Purchase Intention. Country Of Origin Perception and Consumer Perception has a negative influence on Pruchase Intention. Keywords: Country Of Origin, Consumer Perception, Brand Image, Purchase Intention